2019
DOI: 10.3390/ma12142305
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Porous Gold Film Using Graphene Oxide as a Sacrificial Layer

Abstract: An original and simple fabrication process to produce thin porous metal films on selected substrates is reported. The fabrication process includes the deposition of a thin layer of gold on a substrate, spin coating of a graphene oxide dispersion, etching the gold film through the graphene oxide layer, and removing the graphene oxide layer. The porosity of the thin gold film is controlled by varying the etching time, the thickness of the gold film, and the concentration of the graphene oxide dispersion. Images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Various fabrication techniques for thin films on top of flexible COC films have been reported. [185,[217][218][219][220] Alazzam et al [160,[218][219][220] established a method for fabricating thin films of reduced GO (rGO) using plasma-enhanced lift-off, which was then utilized in LOC applications. According to the results, GO adheres effectively to the surface of the COC.…”
Section: Organic Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fabrication techniques for thin films on top of flexible COC films have been reported. [185,[217][218][219][220] Alazzam et al [160,[218][219][220] established a method for fabricating thin films of reduced GO (rGO) using plasma-enhanced lift-off, which was then utilized in LOC applications. According to the results, GO adheres effectively to the surface of the COC.…”
Section: Organic Semiconductorsmentioning
confidence: 99%
“…The COC/GO devices were used to manipulate cells under dielectrophoresis [219] as well as droplet coalescence and manipulation. [160,[218][219][220] Other GO/COC applications have recently been reported. [161,217,[220][221][222][223] Abunahla et al [221,222] reported the memristive behavior of GO and rGO films.…”
Section: Organic Semiconductorsmentioning
confidence: 99%
“…GO is a hydrophilic material widely used in various fields, and it is composed of graphene sheets containing oxygen functional groups. [129,130] These functional groups form hydrogen bonds with water molecules to achieve the purpose of water transportation along with the sheet. Alazzam and Alamoodi [131] proposed a microfluidic device with a patterned GO film.…”
Section: Microfluidic Applications In Separation Of Continuous Liquid...mentioning
confidence: 99%
“…These methods add additional chemicals and treatment steps that may add complexity to the fabrication process of microfluidic devices. Graphene oxide (GO) is another hydrophilic material that is widely used in various fields. , It consists of graphene sheets decorated with oxygen-containing functional groups. These negatively charged functional groups form hydrogen bonds with water molecules facilitating the transport of water along the sheets.…”
Section: Introductionmentioning
confidence: 99%